Analysis of Transformer Protection Systems Using Smart Relays for Electrical Energy Stability - Yuli Prasetyo; Dimas Nur Prakoso; Ryan Wicaksono; Budi Triyono; Santi Triwijaya (International Journal of Science, Engineering, and Information Technology, 2023)
A transformer is an electrical device that is used to change the voltage from one level to another in order to transfer electrical energy from one place to another. One of the main benefits of a transformer is to reduce power loss in the electrical network. Transformers can be used to stabilize the electric voltage and keep the electric voltage within safe limits. The protection system on the transformer is very important to prevent damage or failure to the transformer which can cause disruption of the electricity supply or even fire. This protection will work to cut off electrical connections and prevent damage to the transformer. Overload interference occurs if the current read on the Smart Relay LCD is more than 10 A so that the contactor will work after a disturbance of 5 seconds and the green indicator light will turn off. Whereas for Overheat interference on the transformer if the temperature exceeds 450C then the contactor will work to turn off the system with a duration of 1-2 seconds then the green indicator light and the system will OFF. The voltage drop disturbance occurs if the voltage read on the Smart Relay LCD is less than 15 kV on the primary side of the transformer and less than 300 V on the secondary side of the transformer so that the contactor will work to cut off the voltage after a disturbance occurs for 8-10 seconds then the green indicator light will turn off.